The Effectiveness of Video Media in Religious Learning to Improve Memorization Skills of Children Aged 5–6 Years at Gondanglegi Kindergarten - Ahmad Fathul Allam; Andi Kristanto; Utari Dewi (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to examine the effectiveness of video media in Islamic Religious Education (PAI) learning for early childhood students at PAUD Gondanglegi. The background of this research lies in the challenge of conveying religious concepts in a concrete and enjoyable way for young learners. The research employed classroom action research (CAR) in two cycles involving 20 children aged 4–5 years. Data collection instruments included observation, interviews, and documentation. The results showed a 45% increase in religious concept comprehension after using Islamic animated video media. Children were more enthusiastic, focused, and able to imitate prayers and behaviors presented in the videos. It is concluded that video media is effective in enhancing children's understanding and active participation in PAI learning.